2014
DOI: 10.1177/0022427814560574
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnic, and Gender Divides in Juvenile Court Sanctioning and Rehabilitative Intervention

Abstract: Objectives: Drawing on focal concerns theory, as well as scholarship on the juvenile court's mandate to consider youth culpability and amenability to treatment, we develop hypotheses that seek to examine whether the court will (1) punish Whites less severely and (2) be more likely to intervene with Whites through rehabilitative intervention and, simultaneously, be more punitive and less rehabilitative with minorities, and, in particular, Black males. Method: Florida juvenile court referral data and multinomial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 53 publications
5
71
2
Order By: Relevance
“…We also found that an inmate's incarceration history, designation as a sexual offender, or whether they were incarcerated for a violent offense had no effect on prison officials decision‐making regarding good time. These findings not only run counter to what would be expected under the uncertainty avoidance, attribution, or focal concerns perspectives, but they are also inconsistent with findings derived from studies of judicial sentencing decisions (e.g., Cochran and Mears ; Griffin and Wooldredge ; Johnson ; Spohn and Holleran ; Steffensmeier and Demuth ; Steffensmeier, Ulmer, and Kramer ; Ulmer and Johnson ; Ulmer, Kurlychek, and Kramer ).…”
Section: Discussioncontrasting
confidence: 94%
“…We also found that an inmate's incarceration history, designation as a sexual offender, or whether they were incarcerated for a violent offense had no effect on prison officials decision‐making regarding good time. These findings not only run counter to what would be expected under the uncertainty avoidance, attribution, or focal concerns perspectives, but they are also inconsistent with findings derived from studies of judicial sentencing decisions (e.g., Cochran and Mears ; Griffin and Wooldredge ; Johnson ; Spohn and Holleran ; Steffensmeier and Demuth ; Steffensmeier, Ulmer, and Kramer ; Ulmer and Johnson ; Ulmer, Kurlychek, and Kramer ).…”
Section: Discussioncontrasting
confidence: 94%
“…Studies have interrogated how a young person's race, gender, and age can influence judicial decision-making, including out-of-home placements and length of sentencing, controlling for factors such as crime severity and criminal history (e.g., Bishop, Lieber, & Johnson 2010; Bridges & Steen 1998; Cochran & Mears 2014; Fader, Kurlychek, & Morgan 2014; Guevara, Herz, Spohn 2006). While the disproportionate number of sexual minority girls in juvenile justice system may be in part the result of the explicit and implicit bias of decision-makers, more research is needed to understand the extent to which sexual orientation is salient in juvenile justice processing, and how this relates to other youth characteristics (e.g., gender expression, race, history of mental health problems) and contextual factors (e.g., family support, homelessness history).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the juvenile court has emphasized active intervention in the lives of youth to help them succeed in life. From this perspective, dismissing minor cases from juvenile court is inappropriate and, indeed, would be unjust and inconsistent with the court's mission (Cochran and Mears, 2015;Tanenhaus, 2004). At the same time, informal processing and sanctioning helps, in theory, to ensure that youth receive balanced, individualized intervention rather than excessive punishment (Guarino-Ghezzi and Loughran, 2004;Howell et al, 2014).…”
Section: Potential Benefits Of Civil Citation and Of Diversion More Gmentioning
confidence: 99%